Analisis Program Pelaksanaan Pencegahan dan Pengendalian Gangguan Mental Emosional - Tatisina, Cut Mutia; Nasela, Siti Johri; Tubalawony, Fransina (Universitas Pahlawan Tuanku Tambusai, 2024)
Mental emotional disorders (GME) are mental health problems that affect a person's performance and quality of life. In Indonesia, the prevalence of GME and depression is quite high, but health services for sufferers are still low. In an effort to prevent and control GME, the Maluku Provincial Health Office has conducted a GME Prevention and Control Orientation Workshop. However, GME prevention and control efforts at the Ambon City Health Center have not been running well. This research used a qualitative approach with a multiple case study design. The research informants were the person in charge of mental health and the Head of Puskesmas in Ambon City, with a total of 22 informants. Data collection was conducted through in-depth interviews, observation, and document review. The collected data were analyzed using data reduction techniques to identify emerging patterns and themes. Analysis of the implementation of the GME prevention and control program at the Ambon City Puskesmas involved 12 mental health program holders as informants. Evaluation of program implementation includes the basis of program policy, resources, and supporting and inhibiting factors. The results of the analysis show that the implementation of the GME prevention and control program still needs to be improved. Based on the results of research conducted at the Ambon City Health Center, the implementation of the Mental Emotional Disorder (GME) prevention and control program has not run optimally.